DISKREPANSI ASAS PERADILAN DILAKUKAN DENGAN SEDERHANA CEPAT DAN BIAYA RINGAN DALAM PERKARA GUGATAN PERDATA DI PERADILAN UMUM - Hakim, Rohman (CV. Era Digital Nusantara, 2023)
This study aims to analyze accountability for discrepancies in the application of the principle of justice which is carried out simply, quickly and at low cost in civil cases in general courts. Through the normative-empirical juridical method, this study was carried out in two stages of study, namely the study of the applicable normative law and its application in concrete events to achieve the stated goals. The results of the study explain that the principle of justice is contained in Article 2 paragraph (4) of Law Number 48 of 2009 concerning Judicial Power, namely that it must be carried out simply, quickly, and at a low cost which must be carried out efficiently and effectively and does not neglect thoroughness and scrupulousness in seeking truth and justice. Meanwhile, accountability for discrepancies in the application of the principle of justice for those who do not carry out their obligations to provide services or do not comply with provisions regarding the principles of justice can be subject to sanctions ranging from a verbal warning to dishonorable discharge as a civil servant.